2018
DOI: 10.1111/ejh.13172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of molecular markers in acute myeloid leukemia

Abstract: The recently updated World Health Organization (WHO) Classification of myeloid neoplasms and leukemia reflects the fact that research in the underlying pathogenic mechanisms of acute myeloid leukemia (AML) has led to remarkable advances in our understanding of the disease. Gene mutations now allow us to explore the enormous diversity among cytogenetically defined subsets of AML, particularly the large subset of cytogenetically normal AML. Despite the progress in unraveling the tumor genome, only a small number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 200 publications
(479 reference statements)
0
41
0
2
Order By: Relevance
“…Early studies indicated that the generation of AML is commonly, albeit not always associated with the acquisition by the malignant cells of a variety of chromosome abnormalities. These are now known to reflect different mutations that deregulate proliferation and block the differentiation of primitive normal blood cell precursors, features considered diagnostic of AML ( Kayser and Levis, 2018 ). Additional features of most AMLs include the suppression of residual normal hematopoiesis and a continuing genetic and biological evolution of the leukemic cells.…”
Section: Main Textmentioning
confidence: 99%
“…Early studies indicated that the generation of AML is commonly, albeit not always associated with the acquisition by the malignant cells of a variety of chromosome abnormalities. These are now known to reflect different mutations that deregulate proliferation and block the differentiation of primitive normal blood cell precursors, features considered diagnostic of AML ( Kayser and Levis, 2018 ). Additional features of most AMLs include the suppression of residual normal hematopoiesis and a continuing genetic and biological evolution of the leukemic cells.…”
Section: Main Textmentioning
confidence: 99%
“…Especially, after the application of next generation sequencing (NGS), this emerging technology has narrowed the gap of knowledge in the molecular biology of pediatric AML by discrimination of targeted gene mutations for separate subtype, which may led to the improvement in terms of prognosis prediction and the use of specific and therapeutic intervention 5 . Moreover, identification of major cytogenetic abnormalities (including genome, transcriptome, and epigenome) defined by new technologies allowed more precise risk stratification for intermediate‐risk‐AML 6 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation and courses in AML vary among patients, depending on the type of AML, molecular and immunological features of clonal cells, patient-related variables such as age or comorbidities, and response to treatment. [1][2][3][4][5][6][7][8] In most patients with de novo AML, induction poly-chemotherapy produces complete remission (CR), and many of these CR-patients can be kept in continuous CR by introducing consolidation therapy. Notably, consolidation therapy is applied with the aim to eliminate most or all of the remaining leukemic (stem) cells after remission-induction therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, treatment of several AML variants has substantially improved which is mainly due to the availability of new (targeted) drugs, improved diagnostics, better selection of patients for various therapies (personalized medicine), and advances in HSCT strategies. [3][4][5][6][7][8] Still, however, many patients relapse or have resistant disease. As a result, AML research is still moving and seeking new ways to improve interventional therapies.…”
Section: Introductionmentioning
confidence: 99%